2022
DOI: 10.1007/s10637-022-01304-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CYP3A4/5 and ABC transporter polymorphisms on osimertinib plasma concentrations in Japanese patients with non-small cell lung cancer

Abstract: BackgroundThe effects of polymorphisms in CYP3A4 (20230G > A), CYP3A5 (6986A > G), ABCB1 (1236C > T, 2677G > T/A, 3435C > T), ABCG2 (421C > A), and ABCC2 (-24C > T) on the area under the concentration-time curve (AUC) of osimertinib in 23 patients with non-small cell lung cancer were investigated. MethodsBlood sampling was performed just prior to and at 1, 2, 4, 6, 8, 12, and 24 h after osimertinib administration at the steady-state on day 15 after beginning therapy. ResultsThere were signi cant correlations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
(33 reference statements)
5
4
0
Order By: Relevance
“…The median estimated AUC 0–24 of osimertinib at steady state was consistent or slightly lower than that in previous reports because some patients included in our study received a reduced dose [ 27 , 28 ]. Albumin level was identified as a significant covariate for the clearance of the parent compound and AZ5104 (positive correlation), consistent with a previous report [ 29 ]. C-reactive protein (CRP) is a covariate of osimertinib clearance [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The median estimated AUC 0–24 of osimertinib at steady state was consistent or slightly lower than that in previous reports because some patients included in our study received a reduced dose [ 27 , 28 ]. Albumin level was identified as a significant covariate for the clearance of the parent compound and AZ5104 (positive correlation), consistent with a previous report [ 29 ]. C-reactive protein (CRP) is a covariate of osimertinib clearance [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results also indicated that exposures to the osimertinib parent compound and AZ5104 were associated with grade ≥ 2 diarrhea and increase in creatinine level. Similarly, a previous report suggested a linear relationship between the exposure to the parent compound and the occurrence of diarrhea [ 11 ], whereas another report suggested that exposure to the parent compound and grade ≥ 1 diarrhea were not associated [ 29 ]; thus, exposure to the parent compound may be related to higher grade (grade ≥ 2) diarrhea. The potential mechanism responsible for both diarrhea and creatinine increase may be the activation of chloride secretion as a result of EGFR inhibition [ 36 ].…”
Section: Discussionmentioning
confidence: 87%
“…We did not find a correlation between these genetic polymorphisms and plasma osimertinib concentrations. This finding is in agreement with a previous study, which reported that genetic polymorphisms did not have an effect on plasma drug concentrations (22). Based on these results, ABCB1/ABCG2 genotyping before osimertinib administration might not be necessary to predict its efficacy and adverse events.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to afatinib, osimertinib is a substrate for P-glycoprotein, encoded by ABCB1, and breast cancer resistance protein, encoded by ATP-binding cassette super-family G member 2 (ABCG2), raising the possibility that individual variations in plasma osimertinib concentrations may occur due to genetic polymorphisms. Although Yokota et al reported that ABC transporter polymorphisms did not contribute to individual variability in osimertinib pharmacokinetics, further studies are needed to resolve this question due to a modest number of enrolled patients (22). Therefore, the present study aimed to clarify the relationship of plasma trough concentrations of osimertinib with efficacy, safety, and associated genetic polymorphisms in Japanese patients with NSCLC harboring EGFR mutations.…”
Section: Months P=0029) Plasma Osimertinib Concentrations Adjusted Fo...mentioning
confidence: 90%
See 1 more Smart Citation